Food guide for soccer tips & recipes from the pros - Averbuch, Gloria (Meyer & Meyer Sport, 2010)
This handy how-to food guide addresses the nutrition questions and concerns of soccer athletes of all ages and abilities to help them reach their goals with energy to spare. It includes tasty recipes from some of the world's top women players.